The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/eqe.2873
|View full text |Cite
|
Sign up to set email alerts
|

Site dependence and record selection schemes for building fragility and regional loss assessment

Abstract: Summary When performing loss assessment of a geographically dispersed building portfolio, the response or loss (fragility or vulnerability) function of any given archetype building is typically considered to be a consistent property of the building itself. On the other hand, recent advances in record selection have shown that the seismic response of a structure is, in general, dependent on the nature of the hazard at the site of interest. This apparent contradiction begs the question: Are building fragility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 41 publications
(95 reference statements)
5
60
0
Order By: Relevance
“…Future research could investigate different IMs that are more efficient by reducing the associated dispersion in the resulting demand parameters. Some potential candidates would be those that are not linked solely to the T 1 of the building, such as those recently proposed that define the IM as a function of the spectral demands in range of periods above and below the T 1 .…”
Section: Analysis Resultsmentioning
confidence: 99%
“…Future research could investigate different IMs that are more efficient by reducing the associated dispersion in the resulting demand parameters. Some potential candidates would be those that are not linked solely to the T 1 of the building, such as those recently proposed that define the IM as a function of the spectral demands in range of periods above and below the T 1 .…”
Section: Analysis Resultsmentioning
confidence: 99%
“…It should be noted that behind the choice of such high period, upper bounds for the AvgS a lie in the nonlinear‐elastic nature of the joystick model, which forces the system to remain on the low‐stiffness hardening branch during loading/unloading and reloading, in contrast to the elastic segments of unloading/reloading of an elastic‐hardening system. In general, the concept of combined S a values may also be deemed a strong candidate IM for the seismic risk evaluation of a group of tanks with varying geometry (and thus T i and T c ) . This is an interesting problem that requires thorough investigation and is expected to be covered in a future direction of our research.…”
Section: Intensity Measure Selectionmentioning
confidence: 99%
“…Studies by many researchers have shown that a wide variety of IM s defined according to the general frame of Equation can offer substantial efficiency and sufficiency for building structures …”
Section: Scalar or Vector?mentioning
confidence: 99%
See 1 more Smart Citation
“…If considerable difference exists among the different first mode periods, one should consider using two different definitions of AvgSa, one for low/mid-rise structures (shorter periods) and another for high-rise ones (longer periods), for better fidelity. In any case, ground motion records need to be selected for each definition of AvgSa at a given set of sites [12,13], while mean hazard curves are required for each definition of AvgSa and at each separate site.…”
Section: Verification Examplementioning
confidence: 99%